Authentic relationships: a review of foreign studies - Edamova, A.Y. (Sovremennaâ Zarubežnaâ Psihologiâ, 2023)
The article presents an overview of the research of the phenomenon of authentic relationships in foreign works. The philosophical understanding of the authenticity of the personality (authenticity, loyalty to the true self) is presented, the possible connection between the authenticity of the personality and the quality of interpersonal relationships is substantiated. A separate part of the article is the discussion of studies of authentic (close) relationships. It is pointed out that it is impossible to consider the authenticity of a person without taking into account its effects on human relationships. The spheres in which authenticity can manifest itself are described: romantic, professional, child-parent, friendly relations. The emphasis is placed on the description of authentic leadership (as the most studied area) and romantic relationships (an area for which authenticity is a particularly important predictor). The article presents several psychotherapeutic methods to achieve them, and also describes some of the risks associated with authentic relationships. Since the authenticity of relationships contributes to effective interaction in the personal and professional sphere, there is a need to study and develop development technologies, necessary both for the authenticity of the individual and the authenticity of the relationship. В статье представлен обзор исследований феномена аутентичных отношений в зарубежных работах. Представлено философское понимание аутентичности личности (подлинности, верности истинному Я), обосновывается возможная связь аутентичности личности и качества межличностных отношений. Отдельной частью работы выступает обсуждение исследований собственно аутентичных (подлинных, значимых) отношений. Указывается на невозможность рассмотрения аутентичности личности без учета ее воздействий на человеческие взаимоотношения. Раскрыты сферы, в которых аутентичность может проявляться: романтические, профессиональные, детско-родительские, дружеские отношения. Акцент поставлен на описание аутентичного лидерства (как наиболее изученной сферы), а также романтических отношений (сферы, для которой аутентичность является особо важным предиктором). В работе представлено несколько психотерапевтических методов для их достижения, а также рассмотрены некоторые риски, которые влекут за собой подлинные отношения. Поскольку аутентичность отношений способствует эффективному взаимодействию в личной и профессиональной сфере, возникает необходимость изучения и разработки технологий развития как аутентичности личности, так и аутентичности отношений.